2006
DOI: 10.1080/15563650600584386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subacute Boric Acid Administration on Rat Kidney Tissue

Abstract: Subacute boric acid exposure caused dose-dependent histopathological changes in kidney tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The results from the physical measurement and the apoptotic status from paraffin sections revealed that bone development was depressed by a high dose of boron in group D. Previous studies have shown that a high dose of boron has an adverse effect on creaturely growth and reproduction [35]. A high dosage of boron also results in histopathological degenerative changes, namely in the proximal tubule cells in rat kidney tissue [36]. Finally, a high dose of boric acid (BA) produces testicular lesions that are characterized by inhibited spermiation followed by atrophy in adult rats [37].…”
Section: Appropriate Amount Of Boron Brings Greatest Profitmentioning
confidence: 90%
“…The results from the physical measurement and the apoptotic status from paraffin sections revealed that bone development was depressed by a high dose of boron in group D. Previous studies have shown that a high dose of boron has an adverse effect on creaturely growth and reproduction [35]. A high dosage of boron also results in histopathological degenerative changes, namely in the proximal tubule cells in rat kidney tissue [36]. Finally, a high dose of boric acid (BA) produces testicular lesions that are characterized by inhibited spermiation followed by atrophy in adult rats [37].…”
Section: Appropriate Amount Of Boron Brings Greatest Profitmentioning
confidence: 90%
“…Therefore, with the consideration of medical purpose, the applications of boric acid should be prevented due to the potential lethality and toxicity of borates compound. Besides, explanation and awareness of its toxicity is essential because of the exposure in industrial and consumer exposure to boron (Sabuncuoglu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has both metal and nonmetal characteristics [1][2][3] . This dynamic trace element enters the body in small amounts via food and drink [4,5] . Boron can affect at least 26 different enzyme activities required for energy substrate metabolism [6,7] .…”
Section: Introductionmentioning
confidence: 99%